PENINGKATAN PEMAHAMAN SISWA TENTANG SEJARAH PERSIAPAN KEMERDEKAAN RI DI SD MELALUI METODE DEMONSTRASI - Faridah Faridah (Universitas Tanjungpura, 2022)
Learning Civics in Elementary Schools to enhance students' understanding of the history of Indonesia's independence preparation. To consider and appreciate the material, students are expected to be able to practice and train directly by the group. The application of demonstration methods in Civics Learning is one of the efforts to solve these problems. The purpose of writing this class action is to increase students' understanding of the history of the preparation for Indonesian independence by using a demonstration method in class VI students of SD Negeri 6 Kota Baru. This class action research took place in SD Negeri 6 Kota Baru in class VI, with 16 students.Implementation of activities carried out through two cycles. Before the first cycle is carried out there needs to be pre-action namely identification of the demonstration method, then the first cycle is carried out as the implementation of the demonstration method, the second cycle as theimplementation of the demonstration method. The results of data analysis show that the use of demonstration methods can improve students' abilities. Thus it can be concluded that through the demonstration method can improve students' abilities.